Modelling & Simulation of PV Module Connected with Three-Port DC Converter - Eahraz Ahmad; Faizan A Khan; Prabhat R Sarkar (International Journal of Engineering and Management Research, 2021)
Of the world’s electricity is being generated through conventional sources of energy like coal and atomic energy. People have realized the dire effect of using these fuels, and the amount of CO2 being released into the environment. There has been a shift in emphasis towards cleaner ways of generating electricity in recent years. Solar energy is abundantly available and the cleanest renewable energy source available in the world and is ready to use for a variety of applications, such as the generation of electricity for residential, commercial, or industrial consumption and have become very competitive solutions. It can be seen that there is trend of solar photovoltaics (PV), which has seen rapid growth over the years. The increasing trend of adopting PV system allows consumers to be known as producers or “Prosumers”. This report evaluates how solar PV can be used in combination with a battery bank along with three port converter to fulfill the requirement. Power production from PV cannot be consistent due to factors like the weather although The main benefits of solar power are that it can be easily installed cost of generation is low as there is no requirement for fuel and require very little maintenance Distributed maximum power point tracking (MPPT) and autonomous are achieved with the proposed configuration. The input-port of each TPC is connected to an independent PV energy source to achieve individual MPPT, and the output-ports of these TPCs are connected with load. Fully modular design is achieved by using Simulink/matlab.